Capecitabine in the routine first-line treatment of elderly patients with advanced colorectal cancer - results from a non-interventional observation study. Issue 1 (December 2016) - Stein, Alexander; Quidde, Julia; Schröder, Jan; Göhler, Thomas; Tschechne, Barbara; Valdix, Annette-Rosel; Höffkes, Heinz-Gert; Schirrmacher-Memmel, Silke; Wohlfarth, Tim; Hinke, Axel; Engelen, Andreas; Arnold, Dirk
Abstract Background The purpose of this observational study was to evaluate feasibility, efficacy results and toxicity observations of capecitabine in routine first line treatment of patients with metastatic colorectal cancer, with particular regard of elderly patients (>75 years of age). Methods Patients with colorectal cancer receiving capecitabine as part of their first-line treatment were recorded until detection of disease progression or up to a maximum of 12 cycles on standardized evaluation forms. Additional information on long-term outcomes, progression-free survival, and overall survival were retrieved at two follow-up time points. Obtained data were analyzed with regard to age up to 75 and >75 years of age. There were no specific requirements for patient selection and conduct of therapy, corresponding to the non-interventional nature of the study. Results In total, 1249 evaluable patients were enrolled in Germany. The median age of the study population was 74 years (range: 21–99). Capecitabine-based combination was administered in 56 % of patients in the overall population. The median treatment duration was about 5 months. Severe toxicities occurred rarely without any difference regarding age groups. The most common hematological toxicity was anemia. Gastrointestinal side effects and hand-food-syndrome (HFS) were the most frequent non-hematologic toxicities. Overall response rate (ORR) was significantly higher in the patient group <=75 years compared to patients >75 years of age (38 vs. 32 %, p=0.019). Median progression free survival (PFS 9.7 vs. 8.2 months, p=0.00021) and overall survival (OS 31.0 vs. 22.6 months, p<0.0001) was decreased in elderly patients. Conclusion Efficacy and tolerability of capecitabine treatment either as single drug or in various combination regimens, as proven in randomized studies, could be confirmed in a clinical routine setting. Patients older than 75 years may derive a relevant benefit by first line capecitabine-based treatment with good tolerability.